Sikap Gereja Terhadap Partisipasi Politik dan Relevansinya Bagi Gereja Toraja Mamasa Jemaat Sapankale - Rerung, Alvary Exan; Attu, Juliati (IAKN TORAJA, 2023)
Abstract: This research talks about the high number of unhealthy politics when holding democratic parties in Indonesia. Money politics to the practice of bringing each other down, is still often carried out when democratic parties take place. As a result of this unhealthy politics, it eventually led to disharmony problems that led to divisions in society. This reality occurs in the Toraja Mamasa Church of the Sapankale Congregation. Based on the data obtained through preliminary observations and interviews, the fact that political practices are unhealthy occurs because the church seems passive and does not take action. This is because the church also does not know how to act towards the ongoing political participation. This paper aims to provide an understanding of the Church's attitude towards political participation which is good and right, so that the church can actively express its prophetic voice by participating in politics. Departing from that problem, using qualitative methods, interviews, and literature, the results of this study provide an understanding that politics has good goals and becomes bad if it is no longer oriented to the interests of society. That is why the Church must present itself as a good example in its participation in political dynamics. This will help church members participate in political activities, so as not to cause problems of disharmony and division. Keywords: Church, politics, Sapankale Congregation, disunity This work is licensed under a Creative Commons Attribution- -ShareAlike 4.0 International (CC BY-SA 4.0) Abstrak: Penelitian ini berbicara tentang tingginya angka politik tidak sehat ketika mengadakan pesta demokrasi di Indonesia. Politik uang hingga praktik saling menjatuhkan, masih sering dilakukan ketika pesta demokrasi berlangsung. Akibat dari politik tidak sehat tersebut, akhirnya menimbulkan masalah disharmoni hingga terjadi perpecahan dalam masyarakat. Realitas ini terjadi di Gereja Toraja Mamasa Jemaat Sapankale. Berdasarkan data yang didapatkan melalui hasil observasi awal dan wawancara, fakta bahwa praktik berpolitik tidak sehat terjadi karena gereja terkesan pasif dan tidak melakukan tindakan. Hal itu dikarenakan gereja juga tidak tahu bagaimana seharusnya bersikap terhadap partisipasi politik yang berlangsung. Tulisan ini bertujuan memberikan pemahaman tentang sikap Gereja terhadap partisipasi politik yang baik dan benar, agar gereja bisa secara aktif menyatakan suara kenabiannya dengan ikut berpartisipasi dalam bidang politik. Berangkat dari masalah itu, dengan menggunakan metode kualitatif, wawancara, dan studi pustaka, hasil penelitian ini memberikan pemahaman bahwa politik itu memiliki tujuan yang baik dan menjadi tidak baik jika tidak lagi berorientasi pada kepentingan masyarakat. Itulah sebabnya, Gereja harus memunculkan dirinya sebagai contoh yang baik dalam partisipasinya terhadap dinamika politik. Hal ini akan membantu warga gereja dalam berpartisipasi terhadap kegiatan berpolitik, agar tidak menimbulkan masalah disharmoni hingga perpecahan. Kata Kunci: Gereja, Politik, Jemaat Sapankale, Perpecahan